Two-dimensional metal-chalcogenide films in tunable optical microcavities - Schwarz, S; Dufferwiel, S; Walker, P; Withers, F; Trichet, A; Sich, M; Li, F; Chekhovich, E; Borisenko, D; Kolesnikov, N; Novoselov, K; Skolnick, MS; et al. (American Chemical Society, 2014)
Integration of quasi-two-dimensional (2D) films of metal-chalcogenides in optical microcavities permits new photonic applications of these materials. Here we present tunable microcavities with monolayer MoS2 or few monolayer GaSe films. We observe significant modification of spectral and temporal properties of photoluminescence (PL): PL is emitted in spectrally narrow and wavelength-tunable cavity modes with quality factors up to 7400; a 10-fold PL lifetime shortening is achieved, a consequence of Purcell enhancement of the spontaneous emission rate.